Gangguan Berbahasa pada Penderita Bibir Celah/Sumbing melalui Prespektif Fonologi - Yesi Mariani; Irwan Siagian (Journal on Education, 2023)
This study aims to determine language disorders in patients with cleft lip/cleft from a phonological perspective. This study examines which phoneme pronunciations of patients with cleft lip/cleft lips have the correct phoneme pronunciation and which are not. This study uses a qualitative approach, namely focusing on careful research, namely the pronunciation of phonemes of people with cleft lips. The object of research is the pronunciation of phonemes in patients with cleft lips. The data source for this study was an adult male with the initials S.N who suffered from an upper cleft lip. The data collection technique uses the note-taking method, this technique is by listening to videos that have been uploaded on S.N's social media and noting the important points contained therein. The results of this study were that S.N had difficulty pronouncing words and even pronouncing them with a nasal sound, but there were several consonant words that sounded clear.